Modern concept — renal continuum (acute kidney injury, acute kidney disease, chronic kidney disease) - A. M. Shutov; E. V. Efremova; M. V. Menzorov; V. A. Serov; A. A. Samoshilova (Архивъ внутренней медицины, 2021)
The lectures present the current understanding of the renal continuum, reflecting the relationship between acute kidney injury (AKI), acute kidney disease (AKD) and chronic kidney disease (CKD). The issue of early diagnosis of AKI remains unresolved, despite numerous studies on biomarkers of acute kidney injury. The epidemiology, clinical and prognostic significance of AKD have not been sufficiently studied. Awareness of both doctors and patients about the «renal continuum» and the possibilities of timely diagnosis and prevention of renal complications is required.